Virtual Teaching in the Time of COVID-19: Rethinking Our WEIRD Pedagogical Commitments to Teacher Education - Thomas, M'Balia (Frontiers in Education, 2020)
Teacher Educators confront a professional future in which online instruction will play an increased role in student learning. As instructional activities are delivered online, a critical challenge for teacher educators will be to continue supporting those ideals key to the missions of many Schools and Colleges of Education—the creation of an instructional environment that is culturally responsive, committed to equity and inclusion, and able to support a diverse and “well” student body.